COMMUNICATIVE STRATEGIES IN INTERLANGUAGE - Kadek Yati Fitria Dewi (Universitas Panji Sakti, 2021)
The concept ‘communicative competence’ covers four main aspects: grammatical competence traditionally dealing with syntax; sociolinguistic competence dealing with social appropriateness of communication; discourse competence dealing with cohesive and coherence in discourse; and strategic competence focusing on pragmatic function of communication. Those aspects of communicative competence have received great attention in language and literacy education, particularly in second language learning. However, little attention is given to the ability to employ different tactics by language users in achieving this goal. This paper examines this neglected area of communicative strategic competence and their implications for research and teaching.